IMMUNITY PAS SPORT LEDGER - Oliveira, Marco António Veríssimo (2022)
The global outbreak of Coronavirus (SARS-CoV-2), which in 2020 reached pandemic scale, has been a central topic of debate in our society. Concerns over the ease of transmission of the infection led to the imposition of measures restricting freedom such as curfews, lockdown, general confinement, and trade closure. Technology was one of the tools used to resist the spread of the disease using applications that, on the one hand, track contacts to warn users that were close to someone infected and, on the other hand, provide immunity digital certification. Despite the relevance of these options, end users have no confidence, transparency, and responsibility that the registration and use of their health data are ethical, secure, anonymous, and available through verifiable credentials. Most importantly, it is being used for its primary purpose. Consequently, a solution based on distributed ledger technology, such as blockchain, is introduced in this work to assure the trustworthiness and integrity of users’ data. Since the proposed work embraced user privacy, we conducted a comparative study between blockchains, focusing on permissioned blockchain that includes an authorization abstraction layer and ensures that identifiable participants can only perform specific actions. This work concluded that Hyperledger Fabric was an option that fulfilled all the requirements to develop a platform for the immunity passport ledger. Its modularity and versatility accommodate the requirements for the development of a prototype. This work describes the architecture used in the developed prototype, as well as the blockchain and applications that compose the system. Our proof of concept provides an architecture that can be used to further study scaling , load balancing and performance capabilities.